Rationale for catheter directed therapy in pulmonary embolism - Naidu, Sailen G.; Knuttinen, Martha-Gracia; Kriegshauser, J. Scott; Eversman, William G.; Oklu, Rahmi (Cardiovascular Diagnosis and Therapy, 2017)
Pulmonary embolism (PE) is a widespread health concern associated with major morbidity and mortality. Catheter directed therapy (CDT) has emerged as a treatment option for acute PE adding to the current potential options of systemic thrombolysis or anticoagulation. The purpose of this review is to understand the rationale and indications for CDT in patients with PE. While numerous studies have shown the benefits of systemic thrombolysis compared to standard anticoagulation, these are balanced by the increased risk of major bleeding. With this in mind, CDT has the potential to offer the benefits of systemic thrombolysis and in theory, a reduced risk of bleeding. This article will review current treatment guidelines in both massive and submassive PE evaluating both short and long term benefits. The role of CDT will be highlighted, with an emphasis on efficacy and safety.